Efficacy of Phytopharmaceuticals From the Amazonian Plant Libidibia ferrea for Wound Healing in Dogs - Américo, Ádria Vanessa Linhares dos Santos; Nunes, Kariane Mendes; Assis, Francisco Flávio Vieira de; Dias, Salatiel Ribeiro; Passos, Carla Tatiane Seixas; Morini, Adriana Caroprezo; Araújo, Junior Avelino de; Castro, Kelly Christina Ferreira; Silva, Silvia Katrine Rabelo da; Barata, Lauro Euclides Soares; Minervino, Antonio Humberto Hamad (Frontiers in Veterinary Science, 2020)
We comparatively evaluate two distinct formulations containing 5% of Jucá (Libidibia ferrea) for wound healing in dogs. An excision model study was performed in 11 dogs with three dermal wounds in each animal, which were treated with: (1) topical phytopharmaceutical based on Carbopol (PyC) containing 5% Jucá ethanolic extract; (2) topical phytopharmaceutical based on Astrocaryum murumuru butter (PyM) containing 5% Jucá ethanolic extract; and (3) commercial ointment (control). Wound treatment was carried out on alternated days starting at day (D) one until D21. Macroscopic (all time-points) and histological (D0 and D21) analyses were performed. The antimicrobial activity of Jucá was evaluated through Minimal Inhibitory Concentration (MIC). Phytochemical analysis of Jucá revealed 3.1% phenolic compound content expressed in rutin and the presence of hydrolyzable tannins and flavonoids. The mean wound retraction was 33.7 ± 5.5, 34.0 ± 4.7, and 28.4 ± 4.9 % for PyC, PyM, and control groups, respectively, with higher wound retraction for both herbal-treated groups compared to the control (P < 0.05). Alcoholic extract of Jucá had antimicrobial activity against the microorganisms Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida krusei at different degrees, with MIC ranging from 250 to 16.625 μg/ml. Microscopic evaluation showed that the phytotherapic formulations contributed to better dermal wound healing through wound fibroplasia. The alcoholic extract of Jucá pods has great potential for wound healing in dogs and can be used in the development of commercially viable phytotherapic formulations.